Blood Donor’s Knowledge, Attitude and Practice Towards Blood Donation among Voluntary Blood Donors at Nepal Red Cross Society Central Blood Transfusion Service Centre - Singh, Smriti; Rijal, Tara Devi; Katwal, Barsika (Journal of Nepalgunj Medical College, 2023)
Introduction: Blood donation is the major source of blood as well as components of blood worldwide. Even though there are lots of promising components to substitute blood, a true component for blood and blood components is not available. Donated blood is an essential component in the management of many diseases. It is the core lifesaving component for an individual with loss of large volumes of blood from accidents, hemorrhages, or surgery. Aims: To evaluate the knowledge, attitude and practices of blood donors who visit blood bank. Methods: A cross-sectional study was done among 227 voluntary donors during six different Blood Donation Campaigns from March to October 2023. Results: A total of 227 blood donors participated in this research, with ages ranging from 19 to 60 years, and an average age of 34.7 years with a standard deviation of 8.77. Among all donors, the majority were male (71.4%), with females representing 28.6%. 1.3% of the donors were illiterate, while 26 % were literate. Additionally, 33% hold a secondary-level degree, 31.3 percent have a bachelor’s degree, and 8.4 percent possess a master’s degree or higher. The majority (46.7%) of the voluntary blood donors were from the service sector, 11% were students, 5.3% in business, 3.5%. were engaged in agriculture and 1.8% working in foreign employment. The remaining 31.7% were involved in various other occupations. Conclusion: Almost 1/10th, 5% had adequate knowledge and 72% showed positive attitude related to blood donation in our study the level of blood donation practice was in majority of donor about 89%.